Holocaust Journey : Travelling in Search of the Past. - Gilbert, Martin (RosettaBooks, 2015)
"A travelogue, spanning two weeks, of the essential sites of the Holocaust, by the venerable historian and author ... [A] soul-searching trip" (Kirkus Reviews). In 1996, prominent Holocaust historian Sir Martin Gilbert embarked on a fourteen-day journey into the past with a group of his graduate students from University College, London. Their destination' Places where the terrible events of the Holocaust had left their mark in Europe. From the railway lines near Auschwitz to the site of Oskar Schindler's heroic efforts in Krakow, Poland, Holocaust Journey features intimate personal meditations from one of our greatest modern historians, and is supported by wartime documents, letters, and diaries'as well as over fifty photographs and maps by the author'all of which help interweave Gilbert's trip with his students with the surrounding history of the towns, camps, and other locations visited. The result is a narrative of the Holocaust that ties the past to the present with poignancy and power. "Gilbert ... is a dedicated guide to this difficult material. We can be grateful for his thoroughness, courage and guidance." 'Los Angeles Times Book Review